Dzikir sebagai Metode Terapi pada Korban Penyalahgunaan Narkotika di Majelis Alif Lam Mim Gejlig Kajen Pekalongan - Ali Mustofa (JOUSIP: Journal of Sufism and Psychotherapy, 2021)
The era of globalization cannot be denied, narcotics circulation has spread to remote villages, the targets are mostly teenagers, such as junior high school, high school and college students. Various ways and efforts have been made to overcome drug abuse. However, it turns out that the prevention and treatment of victims of narcotics abuse is not easy, because it does not only involve physiological aspects, but also psychological aspects so that ongoing efforts are needed. This study aims to find out more about the dhikr used by the Alif Lam Mim Council of Gejlig Kajen Pekalongan Village as a method of therapy for victims of narcotics abuse. The research method used is qualitative with phenomenology. The data analysis used in this study is to describe personal experiences with the phenomenon being studied, make a list of important statements, take the important statements and then group them into meaning units or themes, write textural descriptions (what is experienced) from participants' experiences, describe structural descriptions (what is experienced) how the experience happened). The results of the study stated that dhikr is effective as a good method for therapy for victims of narcotics abuse in the Alif Lam Mim Assembly, Gejlig Village, Kajen District, Pekalongan Regency.